The Lorenz curve in economics and econometrics - Christian Kleiber (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
This paper surveys selected applications of the Lorenz curve and related stochastic orders in economics and econometrics, with a bias towards problems in statistical distribution theory. These include characterizations of income distributions in terms of families of inequality measures, Lorenz ordering of multiparameter distributions in terms of their parameters, probability inequalities for distributions of quadratic forms, and Condorcet jury theorems.
Keywords: 519; Lorenz curve; Lorenz order; majorization; income distribution; income inequality; statistical distributions; characterizations; Lorenz-Kurve; Theorie